Latar Belakang Perubahan Kebijakan Pemerintah Jepang terhadap Minoritas Korea (Zainichi Koreans) - HIMAWAN, G.A AMANDA CLARISSA; Nurhayati, Ririn Tri ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Resident Koreans or often referred as Zainichi Koreans, is the largest minority group with foreign origin in Japan, accounting 30% of foreign population. Though a lot of them were born and grew up in Japan, they have faced a long history of discrimination in Japan. One of the biggest disadvantages faced by resident Koreans was fingerprinting practice, started by the enactment of Alien Registration Law in 1952. Another kind of hardship was apparent in the case of pension fund. Resident Koreans, most of them are working in service sector or small companies, were not eligible to get National Pension Funds simply because they are not Japanese. They also could not become a public school teacher due to their nationality. Although Minority Rights Group International still considers resident Koreans as vulnerable, policy-wise, there has been some improvements regarding resident Koreans status and living condition. Fingerprinting practice was abolished in 1991 and went into full enforcement in 1992. National pension plan which initially only accessible by Japanese finally can also be accessed by resident Koreans retiree in 1982. The discrimination in education also began to decrease when the number of universities accepting Korean schools graduates increased. Using Snyder et.al. analytical framework of policy change and putting the concept of gaiatsu and social movements within it, this thesis elaborates that international as well as domestic factors contribute to those policy changes. Japans increasing involvement in international human rights regimes and its effort to improve bilateral relationship with South Korea pressed japan to change its policy towards Zainichi Koreans. But those external pressure will not work as effectively were there no social movements from Zainichi Koreans themselves and support from sympathetic local government.